The Road Back (All Quiet on the Western Front/The Road Back #2) - Erich Maria Remarque (New York Avon Book Division, 1959)
After surviving several horrifying years in the inferno of the Western Front, a young German soldier and his cohorts return home at the end of WW1. Their road back to life in civilian world is made arduous by their bitterness about what they find in post-war society. A captivating story, one of Remarque's best.
Keywords: Fiction; Historical fiction; War novel; Classics